Factors Relatated to the Access to Sources of Fundings of Hopitality Entrepreneurs in Luang Prabang Municipality, Luang Prabang Province - KHATTIGHALATH , Lithigha; HOUANGSENGFAH , Southida; INDAVONG, Dalounny (Souphanouvong University Journal Multidisciplinary Research and Development, 2020)
The objectives of the research are to study 1) . The situations of the entrepreneurship and sources of fundings of hospitality entrepreneurs in Luang Prabang Municipality, Luang Prabang Province, 2). The factors related to the access to fundings of hospitality entrepreneurs in Luang Prabang Municipality, Luang Prabang Province. Questionnaires were used to get anwers from 215 hospitality entrepreneurs in Luang Prabang Municipality, Luang Prabang Province. Chi-Square Statistic was used to analyse the relationships between factors related to the access to fundings of hospitality entrepreneurs. The study shows that, among 215 hospitality entrepreneurs, most of the them invest in guesthouses. In this number sole owners of the guesthouses and have been running this business between 5-10 years. Those who have income between 5 ,000,000-10,000,000. Those with 1-10 employees. Most of the entrepreneurs invest between 100-200 million LAK in their busnesses. Most of the capital are loans from financial institutions. In that, loans of 200-300 million LAK and loans of 3-5 years. Factors related to the access to sources of fundings for hospitality entrepreneurship in Luang Prabang Municipal, Luang Prabang Province, are from financial institutions and the entrepreneurs with has statistical significance at the level of 0.05 while factors regarding to government policy do not have a relationship with sources of fundings with has statistical significance at the level of 0.05. This is due to the fact that financial institutions under the support from the government do not provide credits for hospitality entrepreneurship s, and The government has a policy to encourage financial institutions to provide credits for hospitality entrepreneurships.